(untitled) (Anclajes, 2021)
The article analyzes how Diamela Eltit’s Mano de obra (2002) deals with utopian moments of Chilean history, from the turn of the 20th century through the 1970s. Mano de obra recovers the archival remainders of a dissenting language that was spoken by the historical “others” of the Chilean nation, making it the common tongue in the novel.